2018
DOI: 10.1111/1462-2920.14347
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia modifies thermal preference in Drosophila melanogaster

Abstract: Environmental variation can have profound and direct effects on fitness, fecundity, and host-symbiont interactions. Replication rates of microbes within arthropod hosts, for example, are correlated with incubation temperature but less is known about the influence of host-symbiont dynamics on environmental preference. Hence, we conducted thermal preference (T ) assays and tested if infection status and genetic variation in endosymbiont bacterium Wolbachia affected temperature choice of Drosophila melanogaster. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 78 publications
4
100
17
Order By: Relevance
“…But how has the ancestral Asian strain be replaced? Wolbachia acquisition and persistence in C. obscurior may be driven by selection on the strain that is better adapted to the local environment, perhaps analogous to Wolbachia -driven thermal preferences in Drosophila flies 49,50 . Resolving how w Cobs-BR replaced the putatively ancestral w Cobs-JP strain (which holds the power of CI) requires testing how mixed combinations of host and Wolbachia perform under varying ecological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…But how has the ancestral Asian strain be replaced? Wolbachia acquisition and persistence in C. obscurior may be driven by selection on the strain that is better adapted to the local environment, perhaps analogous to Wolbachia -driven thermal preferences in Drosophila flies 49,50 . Resolving how w Cobs-BR replaced the putatively ancestral w Cobs-JP strain (which holds the power of CI) requires testing how mixed combinations of host and Wolbachia perform under varying ecological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the infection rate has propensity to decline over the last decade in D. melanogaster population in Uman'. Truit et al [24] have shown that infected flies prefer a lower range of temperature than uninfected ones. This behavioral adaptation is likely affecting the accuracy of the estimation of the link between temperature and infection frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of Wolbachia, for example, is negatively affected by host fitness via temperature as well as by other stress factors (e.g. [66][67][68]). Thus, the more stressful conditions of the dry season may reduce the overall fitness of the fly and consequently the Spiroplasma infection densities.…”
Section: Geographic Origin and Seasonalitymentioning
confidence: 99%